Taḥlīlu al Mufradāti al Dakhīlati min al Lughati al Injlīziyyati ilā al Lughati al ‘Arabiyyati fī Taṭbīqi Akhbāri al Taqniyyati wa al Tiknūlūjiyya: Dirāsatun fī ‘Ilmi al Dalālati - Mandaka, Dwi Arian Putra; Khasanah, Mushokhikhul (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2023)
In this thesis the author discusses the absorption vocabulary from English to Arabic in the technology contained in the application